Dihydroartemisinin Induces Growth Arrest and Overcomes Dexamethasone Resistance in Multiple Myeloma - Chen, Ying; Li, Rui; Zhu, Yuqi; Zhong, Sixia; Qian, Jinjun; Yang, Dongqing; Jurczyszyn, Artur; Beksac, Meral; Gu, Chunyan; Yang, Ye (Frontiers in Oncology, 2020)
The discovery of artemisinin (ART) for malaria treatment won the 2015 Nobel Prize in Medicine, which inspired the rediscovery and development of ART for the treatment of other diseases including cancer. In this study, we investigated the potential therapeutic effect of ART and dihydroartemisinin (DHA) on multiple myeloma (MM) cells including primary MM cells and in 5TMM3VT mouse model. Both in vitro and in vivo experiments showed that DHA might be a more promising anti-MM agent with significantly improved efficacy compared to ART. Mechanistic analyses suggested that DHA activated the mitochondrial apoptotic pathway by interacting with ferrous (Fe2+) ions and oxygen to produce reactive oxygen species (ROS). Intriguingly, DHA could reverse the upregulated expression of B-cell lymphoma 2 (Bcl-2) protein, a typical mitochondrial apoptotic marker, induced by dexamethasone (Dexa) in MM. We further demonstrated that DHA treatment could overcome Dexa resistance and enhance Dexa efficacy in MM. Additionally, DHA combined with Dexa resulted in increased ROS production and cytochrome C translocation from the mitochondria to the cytoplasm, resulting in alterations to the mitochondrial membrane potential and caspase-mediated apoptosis. In summary, our study demonstrated that DHA was superior to ART in MM treatment and overcame Dexa resistance both in vitro and in vivo, providing a promising therapeutic strategy for MM therapy.